2018
DOI: 10.7554/elife.31640
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal populations in the occipital cortex of the blind synchronize to the temporal dynamics of speech

Abstract: The occipital cortex of early blind individuals (EB) activates during speech processing, challenging the notion of a hard-wired neurobiology of language. But, at what stage of speech processing do occipital regions participate in EB? Here we demonstrate that parieto-occipital regions in EB enhance their synchronization to acoustic fluctuations in human speech in the theta-range (corresponding to syllabic rate), irrespective of speech intelligibility. Crucially, enhanced synchronization to the intelligibility o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 121 publications
2
30
1
Order By: Relevance
“…Because this area has a native computation that does not easily transfer to another sensory modality, it may therefore rewire itself for distant functions (Bedny, 2017). Some studies, for instance reported an involvement of EVC in high-level linguistic tasks (Ackeren et al, 2018;Amedi, Raz, Pianka, Malach, & Zohary, 2003;Bedny et al, 2011). However, as demonstrated here, the categorical membership of sounds, which may be a proxy for semantic representation, does not explain the representational structure of EVC in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…Because this area has a native computation that does not easily transfer to another sensory modality, it may therefore rewire itself for distant functions (Bedny, 2017). Some studies, for instance reported an involvement of EVC in high-level linguistic tasks (Ackeren et al, 2018;Amedi, Raz, Pianka, Malach, & Zohary, 2003;Bedny et al, 2011). However, as demonstrated here, the categorical membership of sounds, which may be a proxy for semantic representation, does not explain the representational structure of EVC in our study.…”
Section: Discussioncontrasting
confidence: 61%
“…According to recent evidence, blind people might even have enhanced comprehension abilities when it comes to syntactically challenging sentences ( Loiotile et al, 2019 ). This can be attributed to the fact that the occipital lobe of congenitally blind people is responsive to language and other high-level cognitive functions, such as cognitive control, and thus provides additional processing resources for such functions ( Bedny et al, 2011 ; Loiotile et al, 2019 ; Van Ackeren et al, 2018 ). Alternatively, enhanced comprehension of unusually complex sentences could be due to more heavy reliance of language as the unique cue to the meaning of utterances, in contrast to sighted people who often rely on additional (visual) cues ( Loiotile et al, 2019 ).…”
Section: Causal Paradigmsmentioning
confidence: 99%
“…This result suggests that the occipital cortex in early blind is re-organized to extend its integration into conceptual selective networks, highlighting further how visual deprivation impact on the neurobiology of conceptual knowledge. Previous studies have shown that occipital areas in the early blind are recruited for high-level conceptual tasks such as language processing, semantic retrieval and math 42,43,[59][60][61] , and that they increase long-range connectivity with frontal and parietal cortices during rest [42][43][44][45] and inferior temporal cortices during semantic judgments 19 . However, here we showed that early blind seem to rely on enhanced connectivity between occipital cortices and temporoparietal conceptual hubs during conceptual processing.…”
Section: Discussionmentioning
confidence: 99%